ANALISIS SWOT PT. ALCYFA FAMILY GROUP GUNA MENINGKATKAN PENJUALAN - Muhammad Sakti Pratama; Islamuddin Islamuddin (UM. Bengkulu, 2026)
The rapid development of the business world today is evident from the increasing number of new entrepreneurs. These fast changes create uncertainty that affects company operations. In such a highly competitive business environment, entrepreneurs constantly strive to sustain their businesses and compete to achieve their expected goals. Various approaches are used to ensure that their businesses can survive amid existing competition. This study aims to develop effective online and offline marketing strategies to improve sales at PT ALCYFA FAMILY GROUP. By integrating online marketing strategies such as social media, email marketing, and websites with offline marketing strategies such as on-location promotions, partnerships with stores, and promotional events, the company can enhance its visibility, boost sales, and strengthen relationships with customers. The findings of this study provide recommendations for marketing strategies that can be implemented by PT ALCYFA FAMILY GROUP to increase its sales and reinforce its position in the market. This research is descriptive, focusing on identifying and describing online and offline marketing strategies and formulating a marketing strategy plan for PT ALCYFA FAMILY GROUP. The plan is based on the company's internal strengths and weaknesses, as well as external opportunities and threats. SWOT Analysis of PT. ALCYFA FAMILY GROUP to increase sales in an effort to enhance sales performance, in accordance with its internal strengths and weaknesses as well as external opportunities and threats. Keywords: online marketing strategy, offline marketing strategy.